Types and Size Distribution of Parrotfish (Family Scaridae) Caught with Gillnets in the Waters off Taduna Village, Kabaruan Island. - Rumping, Agustiani M. V.; Rondonuwu, Ari B.; Kondoy, Khristin F I.; Lalita, Jans Djoike; Rangan, Jetty K.; Tombokan, Leonard J. (Sam Ratulangi University, 2023)
The objective of this research is to identify the types and size distribution of parrotfish in the waters of Taduna Village. The research was conducted using sampling methods. Samples were collected over a period of two months from the catches landed in Taduna Village by local fishermen. The fishermen used gillnets for their catches. The length of each fish was measured from the tip of the mouth to the end of the tail using a millimeter-scale ruler with a precision of 0.1 cm. The weight of the fish was measured using a digital scale with a resolution of one gram. The length of each species was analyzed using frequency distribution and presented in length and weight histograms. Based on the data obtained from the measurements of Family Scaridae fish, a total of 53 individuals were collected, consisting of 8 species: Chorurus bleekeri (11 individuals), Calotomus carolinus (4 individuals), Chorurus japanensis (6 individuals), Chlorurus microrhinos (2 individuals), Scarus frenatus (16 individuals), Scarus russell (4 individuals), Scarus spinus (5 individuals), and Scarus tricolor (5 individuals). The distribution of Family Scaridae fish in the waters off Taduna Village shows varying lengths and weights for each species. For example, Chorurus bleekeri ranged from 18.9 to 26.5 cm in length and weighed between 150 and 394 grams, Chorurus japanensis had a length distribution between 17.5 and 27.4 cm and weighed from 119 to 465 grams, and Scarus frenatus ranged from 18.3 to 24.5 cm in length and weighed between 117 and 308 grams.